Le goyavier rouge : Psidium cattleyanum var. coriaceum (Mart. ex O. Berg) Kiaersk. une espèce envahissante, à usage multiple en Grande-Comore - Mohamed Mahamoud Charahabil; Leonard Elie Akpo (European Scientific Journal, ESJ, 2018)
The geographical position of the Comoros archipelago conditions an environment conducive to continental biological invasions. In the current context of climate change, with the repeated arrival of strong winds from nearby coasts, the phenomenon is likely to worsen. This study presents the characteristics of the biological invasion of Psidium. cattleyanum var. Coriaceum in Grande-Comore using quantitative structural data of its population and modeling of its ecological niche. The uses of the species and its socio-economic importance were defined by means of a population survey. The overall results revealed the species' invasion status through density, relative frequency, regeneration potential and horizontal distribution model. The modeling of its ecological niche has shown that all the wooded areas of the island are potential sites of the species. Socioeconomic surveys have shown that Psidium. Cattleyanum is a multipurpose species well appreciated by the people. The fight against this invasion very common to all the islands of the southwest of the Indian Ocean faces, in this island of the archipelago of Comoros, a conflict of interest between the conservation of biodiversity and satisfaction the needs of these populations. This work provided reference frames that would allow a better knowledge of the phenomenon for better management.